2019
DOI: 10.1002/eng2.12063
|View full text |Cite
|
Sign up to set email alerts
|

The use of the intensity‐curvature measurement approaches: Applications in magnetic resonance imaging of the human brain

Abstract: This research describes signal processing techniques useful to highlight and contrast enhance human brain vessels detected with magnetic resonance imaging (MRI). The signal is here represented as multiplication between image intensity and the sum of second‐order partial derivatives of the model function fitted to MRI data. The implication of this novel and different concept is the introduction of the new variable called intensity‐curvature. The following six intensity‐curvature measurement approaches (ICMAs) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…T2‐weighted MRI is not indicated for vessel imaging, and in this context, the paper proposes a technique able to improve vessels detection in T2‐MRI. This aspect is not reported elsewhere and is thus the main novelty of this research vs recent developments 27‐30 . Moreover, this research makes a neat progress vs the inverse Fourier transformation procedure reported earlier 28 .…”
Section: Discussion Of the Contributionmentioning
confidence: 61%
See 4 more Smart Citations
“…T2‐weighted MRI is not indicated for vessel imaging, and in this context, the paper proposes a technique able to improve vessels detection in T2‐MRI. This aspect is not reported elsewhere and is thus the main novelty of this research vs recent developments 27‐30 . Moreover, this research makes a neat progress vs the inverse Fourier transformation procedure reported earlier 28 .…”
Section: Discussion Of the Contributionmentioning
confidence: 61%
“…The Z‐Test in Figure 5D shows that the one‐tailed P ‐value is true for all of the bins of the histogram in (B). The ICF calculated from the bivariate linear model function (SRE2D) is the optimal ICF of the six reported, is a k‐space filter 27 and an image space high pass filter 28,30 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations